Analysis of Planning and Budget Consistency on The Quality of Government Agency Performance Accountability Reports in the Simeulue District - Mujahid, Abdullah; darwanis, darwanis; Abdullah, Syukriy (East Asian Journal of Multidisciplinary Research, 2024)
The assessment of the Simeulue Regency Government Agency Performance Accountability System documents for the 2017 - 2022 period still received a sufficient title of "C" (Adequate), while the Government targeted good predicate “B” for the report in the Simeulue Regency Regional Medium Term Development Plan for 2017-2022. The research aims in knowing the extent of planning and budgeting and its impact on performance accountability reports of Simeulue Regency Regional Government agencies. Descriptive qualitative research method was used through interviews with 14 key respondents as the team for preparing the report, consisting of employees in the organizational section of the Regional Secretariat, Regional Development Planning Agency, Regional Financial Management Agency and Inspectorate. The findings show that 82.08% of programs were planned, while the other 17.92% were not, indicating inconsistencies. The implications for the Government Agency Performance Accountability Report have not been fully met according to the recommendations. Improvement is needed for the Government to achieve the targeted value.